2009
DOI: 10.1590/s0100-72032009001000007
|View full text |Cite
|
Sign up to set email alerts
|

Apresentação de resultados de um serviço de rastreamento mamográfico com ênfase na auditoria epidemiológica

Abstract: This study brings important epidemiological data for the audit of mammographic screening, rare among us. Data have been analyzed as compared to what is recommended by the literature, the detection rate and the percentage of minimal and in situ carcinomas found being comparable to the established values, but with the VPP value lower than the ideal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“… 21 The Campinas study cited above found a rate of 0.3%, possibly explained by the fact that 42.2% of the women included in the study were under 50 years of age and that the study only included 93% of subsequent screening. 14 In general, despite the variability in BI-RADS ® 4 and 5 distribution, the detection rate estimated in our study was close to that reported in several programs and studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“… 21 The Campinas study cited above found a rate of 0.3%, possibly explained by the fact that 42.2% of the women included in the study were under 50 years of age and that the study only included 93% of subsequent screening. 14 In general, despite the variability in BI-RADS ® 4 and 5 distribution, the detection rate estimated in our study was close to that reported in several programs and studies.…”
Section: Discussionsupporting
confidence: 89%
“…13 Comparison with previous exams, new incidences and maneuvers must be performed by the radiology service before the definitive BI-RADS ® result is issued. 14 As such, in accordance with what is recommended for this result, the SISCAN recommendation is to perform ultrasound.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation